Comparison the Effectiveness of Cognitive Behavior Training and Educational Perfectionism Schema-based Strategies Training on Academic Buoyancy of High School Female Students - Bahreini Moghim Jiroft, Nasrin; Golparvar, Mohsen; Aghaei, Asghar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Academic buoyancy is an important variable for high school students succession. The present study was conducted with the aim of comparing the effectiveness of cognitive-behavioral training and educational perfectionism schema-based strategies training on academic buoyancy of high school female students. Methods: The study method was quasi-experimental with pre-test-post-test and control group with two-month follow-up. The statistical population of the research includes female high school students in Jiroft province during Fall of year 2021. In the first stage, 48 female high school students were selected as the statistical sample of the study based on the convenience sampling method, and in the next stage, they were divided into three groups through a simple random sampling method (16 students in each group). For data collection, Hosseinchari & Dehghanizadeh ’s academic buoyancy (2012) were completed in three stages: pre-test, post-test and follow up. Cognitive-behavioral training and educational perfectionism schema-based strategies training was performed in 8 sessions (one session per week) for 90 minutes. To analyze the data, repeated measure analysis of variance and Bonferroni post-hoc test was used by SPSS.26. Results: The results of the research indicated that there was a significant difference between cognitive-behavioral training and educational perfectionism schema-based strategies training with control group in academic buoyancy (p<0/001, F=26.11). There is no significant difference between cognitive-behavioral training and educational perfectionism schema-based strategies training in academic buoyancy. Conclusion: It can be concluded that, cognitive-behavioral training and educational perfectionism schema-based strategies training were effective in increasing the academic buoyancy, therefor these training can be used for high school female students.